Significant benthic iron and manganese fluxes into the oxygenated ocean associated with humic substances: Results from benthic chamber experiments in the East Sea (Japan Sea) - Hojong Seo; Guebuem Kim; Heejun Han; Sung-Han Kim; Jae Seong Lee (Marine Chemistry, 2026)

Tracing the contrasting fates of terrestrial and marine organic matter in coastal waters using stable carbon isotopes - Nahyeon Kwon; Hyeong Kyu Kwon; Hyekyung Park; Heejun Han; Kyung-Tae Kim; Jae Seong Lee; Soobin Kim; Guebuem Kim (Marine Pollution Bulletin, 2026)

Dissolved organic matter dynamics in a whale-dominated coastal system: Insights from Península Valdés, Argentina - Luis G. Egea; Rocío Jiménez-Ramos; Valeria C. D'Agostino; Mariana Degrati; Sebastián Giacomino; Guebuem Kim; Heejun Han; Rocío Loizaga (Marine Environmental Research, 2026)

Spatiotemporal variations of dissolved organic matter in coastal groundwater and controlling biogeochemical factors in tidal flats of Incheon, on the west coast of Korea - Hyung-Mi Cho; Gayeon Kim; Minjun Kim; Heejun Han; Jeonghyun Kim; Tae-Hoon Kim; Hyun Je Park (Regional Studies in Marine Science, 2026)

Marginal seas as potential sinks for refractory carbon - Yeongjin Ryu; Heejun Han; Taehee Na; Guebuem Kim; Jeomshik Hwang (Limnology and Oceanography, 2026)
The Yellow Sea (YS) and East China Sea (ECS) are marginal seas in the Northwestern Pacific that receive large amounts of aged, terrestrial organic matter. In this study, we measured dissolved organic carbon (DOC) concentrations and radiocarbon contents (Δ 14 C) in these seas during summer and autumn, extending a previous winter study to provide a more comprehensive understanding of the DOC cycle, including its sources and removal. The significant negative correlation between DOC concentrations or Δ 14 C values and salinity shows that vertical and horizontal water mass mixing between coastal waters and the water intruding to the site from the Northwestern Pacific is the primary control on the distribution of DOC. The Δ 14 C values and the inverse of DOC concentrations show significant negative correlation, suggesting that marine primary production is the dominant DOC source in this region. However, deviations from this correlation imply inputs of aged DOC. Although freshwater input is highest in summer, the effects of aged DOC are greater in autumn and winter. Terrestrial organic matter delivered by rivers is rapidly degraded, and this process likely stimulates marine primary production. In addition, large seasonal differences in Δ 14 C values in Kuroshio‐derived waters indicate significant removal of marine refractory DOC on the continental shelf. The results show that continental shelves have a key role in the removal of terrestrial and marine refractory DOC.

Simultaneous exciton control and electron recycling in pyrene-based stable blue fluorescent organic light-emitting diodes via hybridized local and charge transfer and triplet-triplet fusion mechanisms - Yi Sak Lee; Heejun Nam; You Na Song; Wan Pyo Hong; Won-Sik Han; Taekyung Kim (Chemical Engineering Journal, 2025)

Distributions of Dissolved Trace Metals in the Nakdong River Estuary: Influence of an Estuarine Barrage on Their Geochemical Behaviors - Ijin Lim; Jiwoo Kim; Jumi Kim; Sung-Uk An; Hyung-Mi Cho; Heejun Han; Hojong Seo; Taejin Kim (Ocean Science Journal, 2025)

Manifold embedding of geological and geophysical observations for non-stationary subsurface property estimation using geodesic Gaussian processes - Eungyu Park; Jize Piao; Hyunggu Jun; Yong-Sung Kim; Heejun Suk; Weon Shik Han (Computers & Geosciences, 2025)

P-limited Prokaryotic Heterotrophic Production and Metabolic Balance Between Prokaryotic Carbon Demand and Phytoplankton Primary Production in Summer in the Central Yellow Sea - Bomina Kim; Yong-Jae Baek; Heejun Han; Hyeonji Lee; Seok-Hyun Youn; Jung-Ho Hyun (Ocean Science Journal, 2025)

Large seasonal variations in distributions, sources, and fluxes of dissolved amino acids in the continental shelf water - Hyekyung Park; Guebuem Kim; Nahyeon Kwon; Hanbyul Lee; Heejun Han; Joon-Soo Lee; In-Seong Han (Progress in Oceanography, 2025)

-Spatiotemporal dynamics of nutrients and organic carbon in coastal seawater off Jeju Island: Effects of submarine groundwater discharge (SGD) and geomorphic settings - Heejun Han; Tae-Hoon Kim; Hyung-Mi Cho; Guebuem Kim; Hyeong Kyu Kwon; Minji Lee (Regional Studies in Marine Science, 2025)

Effect of fracture characteristics on groundwater flow adjacent to high-level radioactive waste repository - Won Woo Yoon; Weon Shik Han; Jeonghwan Hwang; Jung-Woo Kim; Kyung Won Chang; Heejun Suk (Journal of Hydrology, 2024)

Semi-analytical solution of single-well push–pull test under transient flow conditions - Heejun Suk; Weon Shik Han; Jui-Sheng Chen; Minjune Yang (Journal of Hydrology, 2023)

Dissolved organic matter in the northwestern Pacific marginal seas: Insight into the distribution of its optical properties - Heejun Han; Hyung Bo Kim; Jeonghyun Kim; Guebuem Kim; Jeomshik Hwang; SungHyun Nam (Frontiers in Marine Science, 2023)
Dissolved organic carbon (DOC) and the optical properties of dissolved organic matter (chromophoric- and fluorescent dissolved organic matter; CDOM and FDOM) were measured to determine the distributions and drivers of DOM in the northwestern Pacific marginal seas, including the East China Sea, the Yellow Sea, and the East/Japan Sea, in August 2020. In this study, the concentrations of DOC and CDOM/FDOM in surface water showed good correlations with salinity, indicating a predominant contribution from the Changjiang River. However, significantly high concentrations of DOC and FDOM were also observed in the central Yellow Sea region, which seems to be produced mainly from the continental shelf-water and enriched over the water residence time of the Yellow Sea, while the lowest concentrations of DOC and CDOM/FDOM were found in high-salinity waters near the southern sea of Korea. In addition, the East/Japan Sea showed relatively low DOC concentrations and high FDOM values. To distinguish the physical mixing and biogeochemical processes of DOM, we estimated the water mass fractions using an optimum multi-parameter analysis with hydrological and DOM parameters of the major water masses in this region. Our results showed that five primary external drivers of DOM distribution were intrusions of (1) the Changjiang diluted water and (2) the Kuroshio Current water in the surface water, the mixing of (3) the Yellow Sea bottom cold water and (4) the Kuroshio sub-surface water in the bottom layer, and (5) upwelling of the East/Japan Sea water. We conclude that the distribution of DOM is significantly influenced by the mixing of multiple water masses, and the optical signature of DOM can be an effective proxy for tracing the origins and characteristics of DOM in this region.

Chemical Speciation of Dissolved Copper in the Nakdong River Estuary and Its Relationship with Humic-Like Fluorescent Dissolved Organic Matter - Hunsub Sim; Ijin Lim; Jumi Kim; Jiwoo Kim; Jong-Sik Ryu; Jun-Ho Lee; Hyung-Mi Cho; Heejun Han; Hojong Seo; Taejin Kim (Ocean Science Journal, 2023)

Diverse sorption capacities and contribution of multiple sorptive sites on illitic clays to assess the immobilization of dissolved cesium in subsurface environments - Jeonghwan Hwang; Weon Shik Han; Sungwook Choung; Jung-Woo Kim; Heejun Suk; Jaehyun Lee (Journal of Hazardous Materials, 2023)

Sediment-Derived Dissolved Organic Matter Stimulates Heterotrophic Prokaryotes Metabolic Activity in Overlying Deep Sea in the Ulleung Basin, East Sea - Jung-Ho Hyun; Bomina Kim; Heejun Han; Yong-Jae Baek; Hyeonji Lee; Hyeyoun Cho; Seok-Hyun Yoon; Guebuem Kim (Frontiers in Marine Science, 2022)
The effects of benthic dissolved organic carbon (DOC) flux on the dynamics of DOC in the deep continental margins (200 – 2000 m depth) is poorly understood. We investigated heterotrophic prokaryotes (hereafter bacteria) production (BP) and the bio-reactive properties of sediment-derived dissolved organic matter (SDOM) to elucidate microbially mediated cause-effect relationships regarding the rapid consumption of dissolved oxygen (DO) and accumulation of humic-like fluorescent DOM (FDOM H ) in the deep-water column (750 – 2000 m depth range) of the Ulleung Basin (UB) in the East Sea. BP in the deep water (2.2 μmol C m -3 d -1 ) of the UB was among the highest reported for various deep-sea sites. The high DOC concentration (55 μM) likely supported the high BP seen in the deep-water column of the UB. Concentrations of DOC and C1 component of the FDOM H , which is indicative of microbial metabolic by-products, were 13-fold and 20-fold greater, respectively, in pore water than in the overlying bottom water, indicating that the sediment in the continental margins is a significant source of DOM in the overlying water column. Fine-scale water sampling revealed that BP near the sediment (0 – 30 m above the seafloor; 2.78 μmol C m -3 d -1 ) was 1.67 times higher than that measured in the water column above (30 – 100 m above the seafloor; 1.67 μmol C m -3 d -1 ). In addition, BP increased in the bottom water incubation amended with SDOM-containing pore water (PW). The results demonstrated that SDOM contains bio-reactive forms of DOM that stimulate heterotrophic microbial metabolism at the expense of oxygen in the bottom water layer. The accumulation of C1 component in both PW-amended and unamended bottom water incubation (i.e., without an extra DOM supply from sediment) further indicated that refractory DOM is produced autochthonously in the water column via heterotrophic metabolic activity. This explains in part the microbially mediated accumulation of excess FDOM H in the deep-water column of the UB. Overall results suggest that the benthic release of bio-reactive DOM may be of widespread significance in controlling microbial processes in the deep-water layer of marginal seas.

Fluorescent Dissolved Organic Matter (FDOM) in the East Sea (Japan Sea): Distributions, Sources, and Sinks - Heejun Han; Hyung-Mi Cho; Hyeong Kyu Kwon; Guebuem Kim (Ocean Science Journal, 2021)

Corrigendum: Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2021)

Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2020)
Shark populations are constantly decreasing owing to environmental destruction and overfishing; thus, sharks are now at a risk of extinction, with 27.9% of shark species classified as endangered on the International Union for Conservation of Nature’s Red List. Sharks are apex predators and a keystone species in balancing the marine food chain; their extinction will create an imbalance of the entire marine ecosystem. Assisted reproductive technology is the last resort for protecting animals facing severe extinction. Here, as a proactive effort toward building a hormone-induced artificial insemination protocol for endangered wild sharks, we identified the possibility of germ cell maturation by administration of Ovaprim ® , a commercially produced synthetic salmon gonadotropin-releasing hormone, and calculated its optimum dosage and injection timing. The experiment was conducted on two shark species— Triakis scyllium and Triaenodon obesus . We found that intramuscular injections of 0.2 mL/kg of Ovaprim ® for male T. scyllium and T. obesus , 0.2 mL/kg + 0.5 mL/kg at a 24 h interval for female T. scyllium , and 0.2 mL/kg + 0.2 mL/kg or 0.2 mL/kg + 0.3 mL/kg at a 24 h interval for female T. obesus were optimal dose protocols. These doses effectively induced the maturation and ovulation of oocytes and the release of semen. Our results confirm that Ovaprim ® is a suitable tool for shark hormone-induced artificial insemination and indicate that this method may enable the conservation of the endangered shark species.

Correction to: Combination of photodynamic therapy (PDT) and anti-tumor immunity in cancer therapy - Hee Sook Hwang; Heejun Shin; Jieun Han; Kun Na (Journal of Pharmaceutical Investigation, 2019)

Combination of photodynamic therapy (PDT) and anti-tumor immunity in cancer therapy - Hee Sook Hwang; Heejun Shin; Jieun Han; Kun Na (Journal of Pharmaceutical Investigation, 2018)
Photodynamic therapy (PDT) is performed using a photosensitizer and light of specific wavelength in the presence of oxygen to generate singlet oxygen and reactive oxygen species(ROS) in the cancer cells. The accumulated photosensitizers in target sites induce ROS generation upon light activation, then the generated cytotoxic reactive oxygen species lead to tumor cell death via apoptosis or necrosis, and damages the target sites which results tumor destruction. As a consequence, the PDT-mediated cell death is associated with anti-tumor immune response. In this paper, the effects of PDT and immune response on tumors are reviewed. Activation of an immune response regarding the innate and adaptive immune response, interaction with immune cells and tumor cells that associated with antitumor efficacy of PDT are also discussed.